Theory of strategy - Gray, Colin S. (New York, NY : Oxford University Press, 2018)
"This book provides a short and accessible introduction to the theory of strategy, examines the general theory of strategy in accordance with 23 key Principles and explains its nature, functions, and intended consequences. 'Theory of Strategy' makes the radical argument that the familiar structure of strategy's general theory (political ends, strategic ways, military means - and assumptions) holds as sound for security at all times and in all places, of human necessity. Strategy is ever-varying in its character, but not in its nature, which is unchanging."--Page 4 of cover.
Cover; Theory of Strategy; Copyright; Dedication; FOREWORD; PREFACE; CONTENTS; 1: Introduction; Purpose; The Need for Theory; The Functions of the Theory of Strategy; TO DEFINE TERMS; TO AID THE ABILITY TO ANTICIPATE BEHAVIOUR; TO HELP UNITE THE OTHERWISE SOMEWHAT ISOLATED INDIVIDUAL ITEMS IN THE THEORY OF STRATEGY; Objections to the Theory of Strategy ... and Replies; Unity and Coherence of the Theory; 2: Argument; The Case for General Theory; Evidence for the General Theory; Limitations of General Theory: Charges and Responses; Possible Limitations; TIMELINES AND CONSEQUENCES THE GENERAL THEORY, OPERATIONS, AND TACTICSGENERALIZATION AND EXCEPTIONS; VARIETY OF AGENTS AND CONDITIONS; THE NUCLEAR EXCEPTION; ARMS CONTROL, THE HOPELESS QUEST; Coherent Theory; 3: Theory (1) Politics and Strategy: Principles 1-7; Introduction; 4: Theory (2) Chaos and Order: Principles 8-13; Introduction; 5: Theory (3) Understanding Complexity: Principles 14-19; Introduction; 6: Theory (4) Coherent Theory: Principles 20-3; Introduction; 7: Strategic History; Concepts; Evidence; Time: The Great Enabler; Strategic Theory: Structure and Evidence; How Strategic Is 'History'? 8: Strategic Sense Politics and Strategy; Politics and Policy; Matters of Consequence; Theory for Realists; Strategic Sense; APPENDIX; BIBLIOGRAPHY; INDEX
Keywords: Strategic culture